Analisis Wacana Kritis Theo Van Leeuwen Pada Pemberitaan Piala Dunia FIFA Qatar 2022 di The Guardian and Al Jazeera - Hannafirsta Seroja Mujapasa (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to reveal the social actors’ representation constructed by The Guardia and, Al Jazeera, in reporting the social actors during the mistreatment of immigrant workers and ‘OneLove’ armband issue during FIFA World Cup Qatar 2022. This study adopted Theo van Leeuwen's (2008) social actor framework which comprises exclusion and inclusion. Exclusion consists of Supresi and backgrounding, while inclusion consists of Aktivasi, Pasivasi, Asimilasi, Diferensiasi, Indeterminasi, Asosiasi, and Nominasi. A qualitative approach was used in this study. The data were collected from fifteen selected news articles published by The Guardian and Al Jazeera. The findings revealed that both news outlets employed exclusion and inclusion sub-strategies in representing the social actors. The Guardian frequently exhibits a critical tone towards FIFA and Qatar in their coverage, potentially reflecting a particular bias, meanwhile Al Jazeera at times attempts to remove or downplay social actors such as FIFA and Qatar, raises questions about their framing and potential biases. In conclusion, the employment of Theo van Leeuwen's social actor framework indicated that news portals excluded and featured social players depending on their goals.